Gardenia Jasminoides Extract as a Potential Neuroprotective Agent in an in Vitro Tauopathy Model - Birekdar, Inas (AUC Knowledge Fountain, 2025)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder marked by the selective loss of neurons in various brain regions, leading to cognitive dysfunction. Neurofibrillary tangles (NFTs), composed of hyperphosphorylated tau protein accumulate within neuronal cells leading to cell death. The development of effective treatments for neurodegenerative diseases (NDs) remains a significant challenge, with neuroprotection emerging as a promising therapeutic strategy to slow disease progression and preserve cognitive function. Objective: This study aims to investigate the potential neuroprotective effect of Gardenia jasminoides fruit extract, which contains geniposide, a biologically active compound known for its neuroprotective properties, in mitigating Tau hyperphosphorylation in an in vitro model of Tauopathy induced by zinc sulfate in SH-SY5Y human neuroblastoma cells. Methods and Results: To assess the neurotoxic effects of zinc sulfate and the potential neuroprotective effects of Gardenia jasminoides extract, an MTT assay, followed by calcein staining were performed. Both assays confirmed that zinc sulfate (100 μM for 4 hours) induced significant neurotoxicity in SH-SY5Y cells, as evidenced by reduced cell viability and increased cellular damage. Pretreatment with Gardenia jasminoides extract (100 μM for 2 hours) significantly decreased the cytotoxic effects of zinc sulfate, improving cell viability and reducing cell damage, indicating the extract's neuroprotective potential. Quantitative PCR (qPCR) analysis of the expression of apoptosis-related genes, showed that zinc sulfate treatment induced significant apoptosis, as evidenced by an increase in BAX/BCL-2 gene expression ratio. However, pretreatment with Gardenia jasminoides extract significantly reduced the expression of these genes, suggesting that the extract mitigated apoptosis induced by zinc sulfate. To assess tau hyperphosphorylation and the activation of key signaling pathways, two complementary techniques were used: immunostaining and cell-based ELISA. Both techniques showed that Zinc sulfate treatment significantly increased the phosphorylation of tau at Ser396, a marker of tau hyperphosphorylation, and this effect was associated with increased GSK-3β activity. In contrast, pretreatment with Gardenia jasminoides extract reduced tau hyperphosphorylation and GSK-3β activity, providing evidence for the extract's ability to modulate tau pathology. Conclusion: Gardenia jasminoides extract demonstrates promising neuroprotective activity in an in vitro model of zinc-induced neurotoxicity and tauopathy, suggesting its potential as a novel therapeutic approach for the treatment of neurodegenerative diseases such as Alzheimer’s disease.